Conceptualizing the Relationship between Islamic Religiosity and Islamic Work Ethics - Abu Hassan Makmun; Desi Yuliana; Tio Devilishanti; Jusnaini Hasni (Jurnal Bisnis dan Manajemen West Science, 2023)
Islam considers working as a virtue and essential for the fulfilment of one’s basic living needs. However, the effect of Islamic religiosity on Islamic work ethics (IWE) has not been thoroughly examined. This study conceptualizes the relationship between Islamic religiosity and IWE. Additionally, it hypothesizes the moderation of income level, education level, and religious education background between Islamic religiosity and IWE. The findings will contribute novel knowledge on the relationship between Islamic religiosity and IWE. Islamic religiosity is expected to positively influence IWE. Income level, religious education background, and education level are expected to positively moderate between Islamic religiosity and IWE.